2018
DOI: 10.1002/pd.5332
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of prenatal whole exome sequencing (PPPWES) study

Abstract: Participants' experience with exome sequence was similar to other prenatal genetic diagnostic tests, except for the longer wait time for results. When probed with hypothetical scenarios, participants desired more results than were provided in the study, including uncertain results that might diagnose the fetal condition. This highlights the need for specialized prenatal genetic counseling to have nuanced discussions of multiple dimensions of uncertainty with implementation of prenatal WES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(97 citation statements)
references
References 25 publications
4
86
0
Order By: Relevance
“…It is also demonstrated in studies in the USA that parents are keen to receive as much information as possible regarding their child's health, even where results are uncertain (Kalynchuk et al, 2015;Wou et al, 2018). One study used hypothetical scenarios to determine the desire for uncertain results and found that while 86% would like to be told about these results, the proportion decreased as the level of uncertainty increased (Wou et al, 2018).…”
Section: Mmentioning
confidence: 99%
“…It is also demonstrated in studies in the USA that parents are keen to receive as much information as possible regarding their child's health, even where results are uncertain (Kalynchuk et al, 2015;Wou et al, 2018). One study used hypothetical scenarios to determine the desire for uncertain results and found that while 86% would like to be told about these results, the proportion decreased as the level of uncertainty increased (Wou et al, 2018).…”
Section: Mmentioning
confidence: 99%
“…Further, these advances allow for multi-disciplinary care planning, and they inform and improve neonatal care and health outcomes. 2 Prenatal trio exome sequencing (trio-ES) is one such advance. Evidence thus far suggests that trio-ES increases diagnostic yield when standard genetic testing (karyotype and microarray) is normal.…”
Section: Introductionmentioning
confidence: 99%
“…One study confirmed the range of challenges that existed, including the need for adequate counseling and informed consent, prenatal variant interpretation, inability to identify a genetic aetiology, and identifying secondary findings in the parents when offering trio testing . The other study clearly showed that parents wanted as much information as possible, including uncertain results that might be related to the diagnosis . These studies highlighted the need for clinicians to understand the power of sequencing, the ethical implications, and parental perceptions, as well as showing the need for specialized genetic counseling and health professional education.…”
Section: Introductionmentioning
confidence: 83%